Syarah Hadis Seputar Fenomena Childfree di Indonesia dengan Pendekatan Ijmali - Jihan Salma Mubarak; Eva Meidi Kulsum; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
This study aims to discuss the phenomenon of child-free hadith perspective. This study uses a qualitative approach through the takhrij and syarah hadith methods with ijmali analysis. The results of this study indicate that the quality of the hadith related to child-free research is assessed as hasan li ghairihi so that it has acceptable consequences (maqbul) and can be practiced for Islamic justification. The discussion of the results of this study explains that the hadith of the Prophet. does not support the child-free attitude except for the case of a married couple experiencing infertility. In fact, cases of infertility need medical assistance to psychological and spiritual assistance. This study concludes that the relevant hadith perspective is used to highlight the symptoms that arise in society, including the child-free phenomenon. The recommendation of this research is the need for in-depth research related to the child-free phenomenon with a more holistic approach.